Traumatismo alveolodentário na dentição decídua: associação do grau de maturidade radicular no momento de injuria e sequelas após acompanhamento longitudinal retrospectivo. - Shqair, Ayah Qassem Ahmad (2012)
This study aimed at investigating the influence of the radicular maturity level of primary teeth in the sequelae of dental trauma as well as the moment that such sequelae take place. Two longitudinal retrospective studies, which collected data from dental records and radiographies of patients with dental trauma in one or both upper central primary incisors. was conducted. In the first one, sequelae such as crown discoloration, pulp canal obliteration and inflammatory root resorption were evaluated in a follow-up period 12-18 months after the trauma, using the registers from 150 patients. In the second study, only intruded and subluxated teeth were included. Clinical and radiographic sequelae such as crown discoloration, fistula, pulp canal obliteration, inflammatory and internal root resorption were evaluated. The data regarding the sequelae were distributed into eight follow-up intervals: 0-30 days; 31-90 days; 91-180 days; 181-365 days; 1 to 2 years; 2 to 3 years; 3 to 4 years and > 4 years. From 150 patients included at the first study, 118 (78.7%) presented luxations and 32 (21.3%) had dental fractures. Shortly after the injury, 13 teeth (9.2%) presented immature roots, 114 (80.3%) presented closed apexes, and 15 of them (10.6%) had visible root resorption. The results showed an association between the radicular maturity level of traumatized teeth and the occurrence pulp obliteration (P = 0.023) and inflammatory root resorption (P = 0.004) after 12-18 months of follow-up period. There was also an association between the type of injury and the occurrence of crown discoloration (P = 0.036) as well as the type of injury and the development of pulp canal obliteration (P = 0.001). Regarding the second study, the sample comprised 99 subluxation cases and 70 intruded teeth. Crown discoloration was the most prevalent sequelae. Among subluxated teeth, more than 50% of inflammatory root resorption, fistula, crown discoloration and pulp obliteration occurred within 180 days after the traumatic injury, however the diagnosis of sequelae still occurred after longer periods. The majority sequelae of intrusion were diagnosed within the 181-365 days and 1-2 years periods but they were still observed after > 4 years follow up period. It can be concluded that the occurrence of trauma sequelae can be determined by the type of injury, as well as by the radicular maturity level of primary teeth at the moment of trauma. Besides, in intrusion and subluxation cases, the diagnosis of sequelae was performed even after the 3-4 years follow-up period.